The Digital and Green Economy: Dual Engines Reshaping Growth, Resilience, and Equity in Emerging Markets - Aduaye-Odiete, Patrick (Global journal of Business and Integral Security, 2026)
The convergence of digital transformation and the green economy is reshaping business strategies and economic policy frameworks worldwide. This paper investigates how the integration of e-commerce, ERP systems, and sustainability principles when jointly adopted drive operational efficiency, competitiveness, and inclusive growth even in emerging markets. Using mixed-methods empirical evidence from Nigerian Small and Medium-Sized Textile Enterprises (SMTEs), the study applies the Technology-Organization-Environment (TOE) and Resource-Based View (RBV) frameworks to evaluate synergies between digital adoption and environmental, social, and governance (ESG) integration. Findings demonstrate that digital-green strategies enhance efficiency, resilience, and financial sustainability, enabling emerging economies to leapfrog traditional development pathways. Policy implications include the design of enabling ecosystems, financial incentives, and capacity-building programmes to accelerate convergence. The paper contributes to literature on sustainable digitalisation and offers actionable insights for policymakers, managers, and development agencies.